Microplastic fate in Arctic coastal waters: accumulation hotspots and role of rivers in Svalbard - Pakhomova, Svetlana; Berezina, Anfisa; Zhdanov, Igor; Yakushev, Evgeniy (Frontiers in Marine Science, 2024)
Little is known about the role of remote and sparsely populated Arctic coastal zones in the microplastic cycle. Distribution of microplastics was studied in the Svalbard fjords in June – July 2022 with the main goal of assessing rivers’ role in the fate of microplastic in Arctic coastal waters. Surface microplastics (0 – 20 cm depth, 500 – 5000 µm size) were sampled with a neuston net in triplicate per study site in parallel with sampling of subsurface microplastics with a pump system (1.5 m depth, 100 – 5000 µm size). The central part of Isfjorden and its several branches covering populated and unpopulated fjords were studied; the sampling was conducted during an intense riverine discharge in all studied sites. Maximum abundance of surface microplastics (71,400 items/km2 or 0.19 iterms/m3, 0.19 mg/m3) was found along the river plume border in the middle of populated Adventfjorden indicating importance of both local sources and surface hydrodynamics in the formation of microplastics accumulation hotspots. All other unpopulated fjords were free of the floating on the sea surface microplastics as river discharge prevented transport of microplastics inside the fjords. The highest concentration of subsurface microplastics was found in the central part of Isfjorden and the lowest – in river plume waters, which also indicates the removal of microplastics from the inner part of fjords during an intensive river discharge. Our results may suggest that Arctic rivers flowing through unpopulated areas bring clean water and thereby reduce level of microplastic pollution in the coastal waters. In contrast to the rest of the world’s ocean, rivers are not the main source of microplastic pollution in the Arctic Ocean.